Solvent-free UV viscosity-reducing adhesive as well as preparation method and application thereof

Through the solvent-free UV viscosity-reducing glue formula, acrylate monomers and oligomers are cross-linked under different wavelengths of ultraviolet light, achieving efficient bonding and viscosity-reducing effects, solving solvent removal in traditional UV viscosity-reducing glue The problems of hazards and poor viscosity reduction effects meet the requirements of green and environmental protection.

CN119161845APending Publication Date: 2024-12-20SHANGHAI RENSU CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411508808.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing UV viscosity reducing glue needs to be baked and eliminated solvents, which can cause harm to factory workers and the environment, and the viscosity reduction effect is poor, making it difficult to meet the needs of green and environmental protection.

Method used

Adopt solvent-free UV viscosity-reducing glue formula, including acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, photoinitiator and tackifying resin, to achieve adhesiveness through 254nm and 350nm ultraviolet light irradiation The bonding and sticking effect will avoid the baking steps.

Benefits of technology

It realizes efficient bonding and viscosity reduction effect of solvent-free UV adhesive reducing glue, reduces baking steps, improves production efficiency, meets the needs of green and environmental protection, and does not leave any residual glue after peeling, and does not damage the adherent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104835070000041
    Figure BDA0005104835070000041
  • Figure BDA0005104835070000042
    Figure BDA0005104835070000042
  • Figure BDA0005104835070000091
    Figure BDA0005104835070000091
Patent Text Reader

Abstract

The invention provides a solvent-free UV viscosity-reducing adhesive as well as a preparation method and application thereof. The solvent-free UV viscosity-reducing adhesive comprises the following components: an acrylate monomer, a urethane acrylate oligomer A, a urethane acrylate oligomer B, a photoinitiator and tackifying resin, the polyurethane acrylate oligomer A is prepared from the following raw materials: 5, 7-dihydroxy-4-methyl coumarin, halogen substituted monohydric alkyl alcohol, 2-ethylhexyl acrylate, isophorone diisocyanate and a hydroxyl-containing acrylate compound. The solvent-free UV viscosity-reducing adhesive provided by the invention does not need to be baked in the coating and production processes of preparing the UV viscosity-reducing adhesive tape, does not generate solvent volatilization, has excellent adhesion after being irradiated by ultraviolet rays of 254nm, has an excellent viscosity-reducing effect after being irradiated by ultraviolet rays of 350nm, and is free of adhesive residues after being stripped.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of viscosity-reducing adhesives, and in particular relates to a solvent-free UV viscosity-reducing adhesive and a preparation method and application thereof. Background Art

[0002] During the processing of optical glass and semiconductors, materials need to be cut and polished, which requires the use of a special tape to fix the materials. After processing, the adhesive force of the tape is sharply reduced by heating or UV irradiation, making it easy to peel off the surface of the material without damaging the material itself. Among them, UV-reducing tape, which makes the tape lose adhesion through UV irradiation, is more widely used.

[0003] UV adhesive tape has good adhesion when cutting, which keeps the material stable and prevents flashing, falling off and edge collapse during cutting and grinding. At the same time, the subsequent use of UV irradiation makes the adhesive force of the tape drop sharply, and it is easy to peel off from the surface of the material without residual glue, easy damage, and no damage to the surface of the material. Irradiation with UV light has a fast reaction time and a short curing time, which effectively improves work efficiency.

[0004] CN115746757A discloses a UV viscosity-reducing adhesive and a preparation method, a UV viscosity-reducing tape and a preparation method, wherein the UV viscosity-reducing adhesive is prepared by the following components in parts by weight: 1500-1800 parts of acrylate main glue, 100-400 parts of reactive monomers, 5-20 parts of catalysts, 1-10 parts of polymerization inhibitors, 20-35 parts of photoinitiators, 8-20 parts of thermal curing agents and a number of diluents; wherein the terminal groups of the reactive monomers simultaneously include epoxy groups and alkenyl groups. The UV viscosity-reducing adhesive provided by the technical solution is polymerized by using reactive monomers containing both epoxy groups and alkenyl groups as terminal groups with the acrylate main glue, reacting the epoxy groups with the carboxyl groups and grafting alkenyl groups on the side chains of the main glue, and when irradiated with ultraviolet light, the acrylate main chain is further cross-linked and cured into a rigid network through the grafted carbon-carbon double bonds, thereby reducing the adhesion and realizing the non-residue adhesive peeling of the UV viscosity-reducing adhesive.

[0005] CN115197663A discloses a UV anti-viscosity adhesive for wafers and a preparation method thereof, and a UV anti-viscosity adhesive tape for wafers. The UV anti-viscosity adhesive for wafers is mainly prepared from the following raw materials in parts by mass: 30-60 parts of a first monomer, 10-30 parts of a second monomer, 2-10 parts of a third monomer, 1-5 parts of a fourth monomer, 0.01-0.5 parts of a polymerization initiator, 100-200 parts of a solvent, 5-15 parts of a multifunctional polyurethane acrylate prepolymer and / or a multifunctional acrylate monomer, and 0.5-2 parts of a photoinitiator. The UV anti-viscosity adhesive for wafers provided by the technical solution can solve the technical problem that the peeling force of the anti-viscosity adhesive after UV treatment is not easy to decrease, which easily leads to residual adhesive particles on the wafer when the UV film is removed, thereby achieving the technical effects of good adhesion, good peeling, and good water resistance of the UV anti-viscosity adhesive, and no residual adhesive and small particles when the UV film on the wafer surface is removed.

[0006] The traditional UV anti-viscosity adhesive tape currently on the market is prepared by coating the UV anti-viscosity adhesive on a substrate, which then needs to be baked to remove a large amount of solvent, which will cause certain harm to factory workers and the environment.

[0007] Therefore, it is necessary to develop a solvent-free UV viscosity-reducing adhesive to meet the needs of green and environmental protection. Summary of the invention

[0008] In view of the shortcomings of the prior art, the object of the present invention is to provide a solvent-free UV viscosity-reducing adhesive and a preparation method and application thereof. The solvent-free UV viscosity-reducing adhesive does not require baking during the coating and production process of preparing the UV viscosity-reducing adhesive tape, does not produce solvent volatilization, has excellent adhesion after 254nm ultraviolet irradiation, has excellent viscosity-reducing effect after 350nm ultraviolet irradiation, and has no residual adhesive after peeling.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a solvent-free UV viscosity-reducing adhesive, wherein the solvent-free UV viscosity-reducing adhesive comprises the following components: an acrylate monomer, a polyurethane acrylate oligomer A, a polyurethane acrylate oligomer B, a photoinitiator and a tackifying resin;

[0011] The raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, halogen-substituted monoalkyl alcohol, isooctyl acrylate, isophorone diisocyanate and a hydroxyl-containing acrylate compound.

[0012] In the present invention, the raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, so that it has the characteristics of coumarin and coumarin derivatives that they can react under ultraviolet light of different wavelengths, can undergo a "2+2" cycloaddition reaction under 350nm ultraviolet light, and can be decrosslinked under 254nm ultraviolet light.

[0013] In the present invention, the solvent-free UV viscosity-reducing adhesive prepared by compounding the polyurethane acrylate oligomer A with acrylate monomers, polyurethane acrylate oligomer B, photoinitiator, and tackifying resin is partially cross-linked after 254nm ultraviolet light irradiation, and has excellent adhesion; after 350nm ultraviolet light irradiation, the coumarin group is cross-linked to form a denser network structure, the colloid becomes hard, the glass transition temperature increases, the pressure sensitivity is lost, the viscosity is greatly reduced, the peeling force decreases, and it has an excellent viscosity-reducing effect, can be easily removed from the surface of the adherend, and no residual glue is generated, and the adherend is not damaged. The solvent-free UV viscosity-reducing adhesive does not need to be baked during the coating and production process of preparing the UV viscosity-reducing tape, and no solvent volatilization is generated. Compared with the traditional solvent-based UV viscosity-reducing adhesive, the baking step is reduced, the efficiency is higher, and it is more environmentally friendly.

[0014] Preferably, the acrylic ester monomer includes any one or a combination of at least two of isobornyl acrylate, N,N-dimethylacrylamide, hydroxyethyl methacrylate, hydroxybutyl propionate, tetrahydrofuran acrylate, ethoxylated tetrahydrofuran acrylate, trihydroxymethylcyclohexyl acrylate, cyclotrimethylolpropane formal acrylate, acetone glycerol acrylate, dodecyl acrylate, isooctyl acrylate, isodecyl acrylate, lauric acrylate or ethoxyethoxyethyl acrylate.

[0015] Preferably, the halogen-substituted monohydric alkyl alcohol comprises chlorine-substituted monohydric alkyl alcohol and / or bromine-substituted monohydric alkyl alcohol.

[0016] Preferably, the halogen-substituted monohydric alkyl alcohol comprises 4-bromo-1-butanol and / or 2-bromoethanol.

[0017] Preferably, the hydroxyl-containing acrylate compound includes any one or a combination of at least two of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA), hydroxypropyl acrylate (HPA), hydroxybutyl acrylate (HBA) or caprolactone acrylate (CA).

[0018] Preferably, the polyurethane acrylate oligomer A is prepared by the following method:

[0019] (1) 5,7-dihydroxy-4-methylcoumarin and a halogen-substituted monoalkyl alcohol are reacted to obtain a compound having a structure as shown in Formula I.

[0020]

[0021] In formula I, R is an alkylene group having 2 to 10 carbon atoms (e.g., 3, 4, 5, 6, 7, 8 or 9).

[0022] (2) The compound having the structure shown in Formula I obtained in step (1) is dissolved in isooctyl acrylate, and then mixed with isophorone diisocyanate, reacted, and a hydroxyl-containing acrylate compound is added for end-capping reaction to obtain the polyurethane acrylate oligomer A.

[0023] In the present invention, the structural unit formed by the compound having the structure shown in Formula I in the polyurethane acrylate oligomer A undergoes crosslinking and decrosslinking reaction under 350nm or 254nm ultraviolet light irradiation as shown in Formula II.

[0024]

[0025] In formula II, represents a connecting bond, and R is an alkylene group having 2 to 10 carbon atoms.

[0026] Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin and the halogen-substituted monoalkyl alcohol in step (1) is 1:(2-2.5), for example, 1:2.1, 1:2.15, 1:2.2, 1:2.25, 1:2.3, 1:2.35, 1:2.4 or 1:2.45, etc.

[0027] Preferably, the mass ratio of the compound having the structure shown in formula I and isophorone diisocyanate in step (2) is 1:(2-3), for example, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8 or 1:2.9, etc.

[0028] Preferably, the mass ratio of the compound having the structure shown in formula I and isooctyl acrylate in step (2) is 1:(0.8-1.2), for example, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1 or 1:1.15, etc.

[0029] Preferably, the mass ratio of isophorone diisocyanate to the hydroxyl-containing acrylate compound in step (2) is 1:(0.6-1.9), for example, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6 or 1:1.8, etc.

[0030] Preferably, the reaction temperature in step (1) is 80-90°C (e.g., 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C or 89°C, etc.), and the reaction time is 16-20h (e.g., 16.5h, 17h, 17.5h, 18h, 18.5h, 19h or 19.5h, etc.).

[0031] Preferably, the reaction temperature in step (2) is 20-40°C (e.g., 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C, etc.), and the reaction time is 0.5-1h (e.g., 0.55h, 0.6h, 0.65h, 0.7h, 0.75h, 0.8h, 0.85h, 0.9h or 0.95h, etc.).

[0032] Preferably, the temperature of the end-capping reaction in step (2) is 40-60°C (for example, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C or 58°C, etc.), and the time is 4-6h (for example, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h or 5.8h, etc.).

[0033] Preferably, the step (1) specifically comprises the following steps: dissolving 5,7-dihydroxy-4-methylcoumarin in a solvent, adding potassium carbonate, adding dropwise a halogen-substituted monoalkyl alcohol, reacting at 80-90°C (e.g., 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C or 89°C, etc.) for 16-20h (e.g., 16.5h, 17h, 17.5h, 18h, 18.5h, 19h or 19.5h, etc.), separating and purifying to obtain the polyurethane acrylate oligomer A.

[0034] Preferably, the solvent comprises dimethylformamide (DMF).

[0035] Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin to the solvent in step (1) is 1:(18-22), for example, 1:18.5, 1:19, 1:19.5, 1:20, 1:20.5, 1:21 or 1:21.5, etc.

[0036] Preferably, the mass ratio of 5,7-dihydroxy-4-methylcoumarin to potassium carbonate in step (1) is 1:(7-10), for example: 1:7.5, 1:8, 1:8.5, 1:9 or 1:9.5, etc.

[0037] Preferably, the step (2) specifically comprises the following steps: dissolving the compound having the structure shown in formula I in isooctyl acrylate, mixing with a catalyst and isophorone diisocyanate, reacting at 20 to 40° C. for 0.5 to 1 h, adding a hydroxyl-containing acrylate compound and performing a capping reaction at 40 to 60° C. for 4 to 6 h to obtain a compound having the structure shown in formula I.

[0038] Preferably, the catalyst comprises dibutyltin dilaurate.

[0039] Preferably, the mass ratio of the compound having the structure shown in Formula I to the catalyst is 1:(0.005-0.01), for example, 1:0.0055, 1:0.006, 1:0.0065, 1:0.007, 1:0.0075, 1:0.008, 1:0.0085, 1:0.009 or 1:0.0095, etc.

[0040] The present invention has no special restrictions on the selection of polyurethane acrylate oligomer B, and all polyurethane acrylate oligomers commonly used in photocurable adhesives in the art are applicable, including but not limited to CN9021NS of Sartomer and / or 2800 of Baojun Chemical.

[0041] Preferably, the photoinitiator includes any one or a combination of at least two of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, methyl benzoylformate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, benzoin dimethyl ether, dimethylbenzil ketal or benzophenone, and more preferably a combination of 1-hydroxycyclohexyl phenyl ketone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0042] Preferably, the tackifying resin includes any one of C5 petroleum resin, hydrogenated C5 petroleum resin, modified rosin ester resin or modified terpene resin, or a combination of at least two thereof, and more preferably C5 petroleum resin.

[0043] Exemplarily, the C5 petroleum resin includes C5 petroleum resin FTR-6100 produced by Mitsui Chemicals; and the modified rosin ester resin includes modified rosin ester resin 146 produced by Guangzhou Kemao.

[0044] Preferably, the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 38 to 55 parts (e.g., 40, 42, 44, 46, 48, 50, 52 or 54 parts) of acrylate monomers, 16 to 32 parts (e.g., 18, 20, 22, 24, 26, 28 or 30 parts) of polyurethane acrylate oligomer A, 18 to 30 parts (e.g., 20, 22, 24, 26 or 28 parts) of polyurethane acrylate oligomer B, 2 to 5 parts (e.g., 2.5, 3, 3.5, 4 or 4.5 parts) of photoinitiator and 5 to 10 parts (e.g., 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9 or 9.5 parts) of tackifying resin.

[0045] In a second aspect, the present invention provides a method for preparing the solvent-free UV viscosity-reducing adhesive as described in the first aspect, the preparation method comprising the following steps: mixing acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, a photoinitiator and a tackifying resin to obtain the solvent-free UV viscosity-reducing adhesive.

[0046] Preferably, the mixing specifically includes mixing acrylate monomers, polyurethane acrylate oligomer A, and polyurethane acrylate oligomer B, and then adding a photoinitiator and a tackifying resin to mix.

[0047] In a third aspect, the present invention provides a UV anti-viscosity tape, wherein the UV anti-viscosity tape comprises a UV anti-viscosity adhesive layer made of the solvent-free UV anti-viscosity adhesive as described in the first aspect.

[0048] Preferably, the thickness of the UV anti-viscosity adhesive layer is 20 to 50 μm (for example, 23 μm, 26 μm, 29 μm, 31 μm, 34 μm, 37 μm, 40 μm, 43 μm, 46 μm or 49 μm, etc.).

[0049] Preferably, the UV anti-adhesion tape further comprises a substrate layer.

[0050] Preferably, the substrate layer includes a polyolefin film (PO film) or a polyethylene terephthalate film (PET film).

[0051] Preferably, the thickness of the substrate layer is 50-75 μm, for example, 53 μm, 56 μm, 59 μm, 62 μm, 65 μm, 68 μm, 71 μm or 74 μm.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] In the present invention, the solvent-free UV viscosity-reducing adhesive prepared by compounding polyurethane acrylate oligomer A with acrylate monomers, polyurethane acrylate oligomer B, photoinitiator, and tackifying resin has excellent adhesion after 254nm ultraviolet light irradiation; after 350nm ultraviolet light irradiation, it has excellent viscosity-reducing effect, can be easily removed from the surface of the adherend, and will not produce residual glue and damage the adherend. The 180° peeling force of the UV viscosity-reducing tape is ≥12N / inch, and viscosity reduction occurs after 350nm ultraviolet light irradiation. The 180° peeling force after viscosity reduction is ≤1.5N / inch, and there is little or no residual glue on the surface of the stainless steel plate after peeling. Preferably, the 180° peeling force of the UV viscosity-reducing tape is ≥14N / inch, and viscosity reduction occurs after 350nm ultraviolet light irradiation. The 180° peeling force after viscosity reduction is ≤0.7N / inch, and there is no residual glue on the surface of the stainless steel plate after peeling. The solvent-free UV viscosity-reducing adhesive does not require baking during the coating and production process of preparing the UV viscosity-reducing adhesive tape, and does not generate solvent volatilization. Compared with traditional solvent-based UV viscosity-reducing adhesives, the baking step is reduced, and the efficiency is higher and more environmentally friendly. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Preparation Example 1

[0056] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-1, and the polyurethane acrylate oligomer A-1 is prepared by the following method:

[0057] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 20 parts by weight of dimethylformamide, add 7 parts by weight of potassium carbonate, dropwise add 2.1 parts by weight of 2-bromoethanol, react at 85° C. for 19 hours, separate and purify to obtain a compound having a structure as shown in Formula I-1;

[0058]

[0059] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-1 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.005 parts by weight of dibutyltin dilaurate dropwise, add 2.25 parts by weight of isophorone diisocyanate and mix, react at 20°C for 1 hour, add 0.6 parts by weight of hydroxyethyl acrylate and carry out end-capping reaction at 40°C for 6 hours until the isocyanate group is completely reacted, thereby obtaining the polyurethane acrylate oligomer A-1.

[0060] Preparation Example 2

[0061] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-2, and the polyurethane acrylate oligomer A-2 is prepared by the following method:

[0062] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 18 parts by weight of dimethylformamide, add 8 parts by weight of potassium carbonate, dropwise add 2.5 parts by weight of 4-bromo-1-butanol, react at 80° C. for 20 hours, separate and purify to obtain a compound having a structure as shown in Formula I-2;

[0063]

[0064] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-2 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.008 part by weight of dibutyltin dilaurate dropwise, add 2.25 parts by weight of isophorone diisocyanate and mix, react at 30° C. for 50 min, add 0.4 parts by weight of hydroxyethyl methacrylate and 0.4 parts by weight of hydroxypropyl acrylate and carry out end-capping reaction at 50° C. for 5 h, until the isocyanate group is completely reacted, to obtain the polyurethane acrylate oligomer A-2.

[0065] Preparation Example 3

[0066] This preparation example provides a polyurethane acrylate oligomer A, specifically a polyurethane acrylate oligomer A-3, and the polyurethane acrylate oligomer A-3 is prepared by the following method:

[0067] (1) Dissolve 1 part by weight of 5,7-dihydroxy-4-methylcoumarin in 22 parts by weight of dimethylformamide, add 9 parts by weight of potassium carbonate, dropwise add 2.5 parts by weight of 2-bromoethanol, react at 90° C. for 16 hours, separate and purify to obtain a compound having a structure as shown in Formula I-1;

[0068]

[0069] (2) Dissolve 1 part by weight of the compound having the structure shown in Formula I-1 obtained in step (1) in 1 part by weight of isooctyl acrylate, add 0.01 part by weight of dibutyltin dilaurate dropwise, add 2.28 parts by weight of isophorone diisocyanate and mix, react at 40°C for 0.5h, add 1.6 parts by weight of caprolactone acrylate and carry out end-capping reaction at 60°C for 4h until the isocyanate group is completely reacted, thereby obtaining the polyurethane acrylate oligomer A-3.

[0070] Example 1

[0071] The present embodiment provides a solvent-free UV viscosity-reducing adhesive and a preparation method thereof and a UV viscosity-reducing adhesive tape, wherein the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 50 parts of acrylate monomers, 18 parts of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1), 26 parts of polyurethane acrylate oligomer B (CN9021NS of Sartomer), 1 part of 1-hydroxycyclohexyl phenyl ketone, 2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and 9 parts of tackifier resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals);

[0072] The acrylic acid ester monomer is composed of 20 parts by weight of ethoxyethoxyethyl acrylate, 6 parts by weight of isobornyl acrylate, 10 parts by weight of hydroxybutyl acrylate and 14 parts by weight of isooctyl acrylate.

[0073] The preparation method of the solvent-free UV viscosity-reducing adhesive comprises the following steps: mixing acrylate monomers, polyurethane acrylate oligomer A, and polyurethane acrylate oligomer B, and then stirring and mixing with 1-hydroxycyclohexyl phenyl ketone, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide and tackifying resin until the mixture is stirred evenly without insoluble particles, thereby obtaining the solvent-free UV viscosity-reducing adhesive.

[0074] The UV anti-viscosity tape comprises a substrate layer and a UV anti-viscosity adhesive layer, wherein the substrate layer is a PET film with a thickness of 50 μm, and the UV anti-viscosity adhesive layer is prepared by using the above-mentioned solvent-free UV anti-viscosity adhesive and has a thickness of 30 μm. The UV anti-viscosity adhesive layer is prepared by the following method: the above-mentioned solvent-free UV anti-viscosity adhesive is coated on the surface of the PET film, and cured by using 254 nm ultraviolet light with an energy of 1500 mJ / cm 2 , and obtain the UV anti-viscosity tape.

[0075] Example 2

[0076] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing adhesive tape, which differs from Example 1 only in that the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 40 parts of acrylate monomers, 30 parts of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-2 provided in Preparation Example 2), 20 parts of polyurethane acrylate oligomer B (CN9021NS of Sartomer), 2 parts of 1-hydroxycyclohexyl phenyl ketone, 2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 6 parts of tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals); the above-mentioned acrylate monomers are composed of 24 parts by weight of isooctyl acrylate, 10 parts by weight of tetrahydrofuran acrylate, and 6 parts by weight of N,N-dimethylacrylamide, and other conditions are the same as those in Example 1.

[0077] Example 3

[0078] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing adhesive tape, which differs from Example 1 only in that the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 44 parts of acrylate monomers, 28 parts of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-3 provided in Preparation Example 3), 20 parts of polyurethane acrylate oligomer B (CN9021NS of Sartomer), 3 parts of 1-hydroxycyclohexyl phenyl ketone, 2 parts of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 7 parts of tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals); the above-mentioned acrylate monomers are composed of 20 parts by weight of isooctyl acrylate, 10 parts by weight of ethoxylated tetrahydrofuran acrylate, 5 parts by weight of N,N-dimethylacrylamide, and 9 parts by weight of acetone glycerol acrylate, and other conditions are the same as those in Example 1.

[0079] Example 4

[0080] The present embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing adhesive tape, which differs from Example 1 only in that the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 46 parts of acrylate monomers, 18 parts of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1), 28 parts of polyurethane acrylate oligomer B (Baojun Chemical 2800), 1 part of 1-hydroxycyclohexyl phenyl ketone, 1 part of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 8 parts of tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals); the above-mentioned acrylate monomers are composed of 20 parts by weight of isooctyl acrylate, 8 parts by weight of hydroxyethyl methacrylate, 9 parts by weight of isobornyl acrylate, and 9 parts by weight of dodecyl acrylate, and other conditions are the same as in Example 1.

[0081] Example 5

[0082] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape, which differs from Example 1 only in that 1 part by weight of 1-hydroxycyclohexyl phenyl ketone and 2 parts by weight of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are replaced with 3 parts by weight of 1-hydroxycyclohexyl phenyl ketone, and other conditions are the same as those in Example 1.

[0083] Example 6

[0084] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape, which differs from Example 1 only in that 1 part by weight of 1-hydroxycyclohexyl phenyl ketone and 2 parts by weight of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are replaced with 3 parts by weight of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and other conditions are the same as those in Example 1.

[0085] Example 7

[0086] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape, which differs from Example 1 only in that 1 part by weight of 1-hydroxycyclohexyl phenyl ketone and 2 parts by weight of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide are replaced by 3 parts by weight of 2-isopropylthioxanthone, and other conditions are the same as those in Example 1.

[0087] Example 8

[0088] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape. The only difference between this embodiment and Example 1 is that the tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals) is replaced with a tackifying resin of the same quality (modified rosin ester resin 146 of Guangzhou Kemao), and other conditions are the same as those in Example 1.

[0089] Example 9

[0090] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape. The only difference between this embodiment and Example 1 is that the weight fraction of the polyurethane acrylate oligomer A (the polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 14 parts, and the other conditions are the same as those in Example 1.

[0091] Example 10

[0092] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape. The only difference between this embodiment and Example 1 is that the weight fraction of the polyurethane acrylate oligomer A (the polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 34 parts, and the other conditions are the same as those in Example 1.

[0093] Embodiment 11

[0094] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape. The difference between this embodiment and Example 1 is that the weight fraction of polyurethane acrylate oligomer B (CN9021NS of Sartomer) is adjusted to 16 parts, and other conditions are the same as those in Example 1.

[0095] Example 12

[0096] This embodiment provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape. The difference between this embodiment and Example 1 is that the weight fraction of polyurethane acrylate oligomer B (CN9021NS of Sartomer) is adjusted to 32 parts, and other conditions are the same as those in Example 1.

[0097] Example 13

[0098] This embodiment provides a solvent-free UV viscosity-reducing adhesive and a preparation method thereof and a UV viscosity-reducing tape. The only difference between this embodiment and Example 1 is that the weight fraction of the tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals) is adjusted to 3 parts, and other conditions are the same as those of Example 1.

[0099] Embodiment 14

[0100] This embodiment provides a solvent-free UV viscosity-reducing adhesive and a preparation method thereof and a UV viscosity-reducing tape. The only difference between this embodiment and Example 1 is that the weight fraction of the tackifying resin (C5 petroleum resin FTR-6100 of Mitsui Chemicals) is adjusted to 12 parts, and other conditions are the same as those of Example 1.

[0101] Comparative Example 1

[0102] This comparative example provides a solvent-free adhesive, a preparation method thereof, and an adhesive tape, which differs from Example 1 only in that the polyurethane acrylate oligomer A is not added, the weight portion of the polyurethane acrylate oligomer B (CN9021NS of Sartomer) is adjusted to 44 parts, and other conditions are the same as those in Example 1.

[0103] Comparative Example 2

[0104] This comparative example provides a solvent-free UV viscosity-reducing adhesive, a preparation method thereof, and a UV viscosity-reducing tape, which differs from Example 1 only in that no polyurethane acrylate oligomer B is added, and the weight proportion of polyurethane acrylate oligomer A (polyurethane acrylate oligomer A-1 provided in Preparation Example 1) is adjusted to 44 parts, and other conditions are the same as those in Example 1.

[0105] The UV adhesive tapes provided in Examples 1-14 and Comparative Example 2 and the tape provided in Comparative Example 1 were tested as follows:

[0106] 180° peel force test: The UV adhesive tape was pasted on a stainless steel plate (SUS), and rolled back and forth three times with a 1kg roller. After leaving it for 10 minutes, a 180° peel force test was performed in accordance with GB / T 2792-2014 at a peeling speed of 300 mm / min.

[0107] After debonding, peeling force test: The UV debonding tape was pasted on a stainless steel plate (SUS), and rolled back and forth three times with a 1kg roller. After leaving it for 10 minutes, it was irradiated with 350nm UV light for 1 minute with an energy of 12000mJ / cm 2 After cooling to room temperature, a 180° peeling force test was performed according to GB / T 2792-2014 at a peeling speed of 300 mm / min. After peeling, observe whether there is residual glue on the surface of the stainless steel plate.

[0108] The test results are shown in Table 1 below.

[0109] Table 1

[0110]

[0111]

[0112] It can be seen from the contents of Table 1 that the 180° peel force of the UV viscosity-reducing tape provided in Examples 1-14 is ≥12 N / inch, viscosity reduction occurs after irradiation with 350 nm ultraviolet light, and the 180° peel force after viscosity reduction is ≤1.5 N / inch, and there is little or no residual adhesive on the surface of the stainless steel plate after peeling.

[0113] Compared with Example 1, if the weight fraction of polyurethane acrylate oligomer A is too small (Example 9), the crosslinking density of the UV adhesive tape is not high enough after being irradiated with 350nm ultraviolet light, so that the UV adhesive tape still retains a part of the pressure sensitivity and has a large peeling force.

[0114] Compared with Example 1, if the weight fraction of the polyurethane acrylate oligomer A is too large (Example 10), the peeling force of the UV-reducing adhesive tape formed after irradiation with 254 nm ultraviolet light is relatively small.

[0115] Compared with Example 1, if the weight fraction of the polyurethane acrylate oligomer B is too small (Example 11), the UV viscosity-reducing adhesive still has a low crosslinking density even after being cured twice by 254 nm ultraviolet light irradiation and 350 nm ultraviolet light irradiation, and is more likely to produce residual adhesive.

[0116] Compared with Example 1, if the weight fraction of polyurethane acrylate oligomer B is too much (Example 12), the crosslinking density of the UV anti-viscosity adhesive after the first curing by 254nm ultraviolet light irradiation is too high, the pressure sensitivity is reduced, the 180° peel force is too low, and the UV anti-viscosity adhesive tape has a poor fixing and protective effect.

[0117] Compared with Example 1, if the weight fraction of the tackifying resin is too small (Example 13), the 180° peeling force of the UV detackifying adhesive after the first curing by 254nm ultraviolet light irradiation is too low, and the UV detackifying adhesive tape has a poor fixing and protective effect.

[0118] Compared with Example 1, if the weight portion of the tackifying resin is too much (Example 14), the tackifying resin does not participate in crosslinking. Excessive tackifying resin improves the peeling force of the UV viscosity-reducing tape, but is more likely to produce residual adhesive.

[0119] Compared with Example 1, if polyurethane acrylate oligomer A is not added (Comparative Example 1), the prepared tape cannot produce viscosity reduction under 350nm ultraviolet light irradiation; if polyurethane acrylate oligomer B is not added (Comparative Example 2), the prepared UV viscosity-reducing tape has a small peeling force after 254nm ultraviolet light irradiation and cannot be used. It can be seen that in the present invention, the UV viscosity-reducing tape prepared by compounding polyurethane acrylate oligomer A and polyurethane acrylate oligomer B has better performance.

[0120] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a solvent-free UV viscosity-reducing adhesive and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A solvent-free UV viscosity-reducing adhesive, characterized in that: The solvent-free UV viscosity-reducing adhesive comprises the following components: acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, a photoinitiator and a tackifying resin; The raw materials for preparing the polyurethane acrylate oligomer A include 5,7-dihydroxy-4-methylcoumarin, halogen-substituted monoalkyl alcohol, isooctyl acrylate, isophorone diisocyanate and a hydroxyl-containing acrylate compound.

2. The solvent-free UV viscosity-reducing adhesive according to claim 1, characterized in that: The acrylic ester monomers include any one or a combination of at least two of isobornyl acrylate, N,N-dimethylacrylamide, hydroxyethyl methacrylate, hydroxybutyl propionate, tetrahydrofuran acrylate, ethoxylated tetrahydrofuran acrylate, trihydroxymethylcyclohexyl acrylate, cyclotrimethylolpropane formal acrylate, acetone glycerol acrylate, dodecyl acrylate, isooctyl acrylate, isodecyl acrylate, lauric acrylate or ethoxyethoxyethyl acrylate.

3. The solvent-free UV viscosity-reducing adhesive according to claim 1 or 2, characterized in that: The halogen-substituted monohydric alkyl alcohol includes chlorine-substituted monohydric alkyl alcohol and / or bromine-substituted monohydric alkyl alcohol; Preferably, the halogen-substituted monohydric alkyl alcohol comprises 4-bromo-1-butanol and / or 2-bromoethanol; Preferably, the hydroxyl-containing acrylate compound includes any one or a combination of at least two of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxybutyl acrylate or caprolactone acrylate; Preferably, the polyurethane acrylate oligomer A is prepared by the following method: (1) reacting 5,7-dihydroxy-4-methylcoumarin with a halogen-substituted monoalkyl alcohol to obtain a compound having a structure as shown in Formula I; In formula Ⅰ, R is an alkylene group having 2 to 10 carbon atoms; (2) The compound having the structure shown in Formula I obtained in step (1) is dissolved in isooctyl acrylate, and then mixed with isophorone diisocyanate, reacted, and a hydroxyl-containing acrylate compound is added for end-capping reaction to obtain the polyurethane acrylate oligomer A.

4. The solvent-free UV viscosity-reducing adhesive according to claim 3, characterized in that: The mass ratio of the 5,7-dihydroxy-4-methylcoumarin and the halogen-substituted monoalkyl alcohol in step (1) is 1:(2-2.5); Preferably, the mass ratio of the compound having the structure shown in formula I to isophorone diisocyanate in step (2) is 1:(2-3); Preferably, the mass ratio of the compound having the structure shown in formula I to isooctyl acrylate in step (2) is 1:(0.8-1.2); Preferably, the mass ratio of isophorone diisocyanate to the hydroxyl-containing acrylate compound in step (2) is 1:(0.6-1.9); Preferably, the reaction temperature in step (1) is 80-90°C and the reaction time is 16-20h; Preferably, the reaction temperature in step (2) is 20-40° C. and the reaction time is 0.5-1 h; Preferably, the temperature of the end-capping reaction in step (2) is 40-60° C. and the time is 4-6 hours.

5. The solvent-free UV viscosity-reducing adhesive according to claim 3 or 4, characterized in that: The step (1) specifically comprises the following steps: dissolving 5,7-dihydroxy-4-methylcoumarin in a solvent, adding potassium carbonate, dripping a halogen-substituted monoalkyl alcohol, reacting at 80 to 90° C. for 16 to 20 hours, separating and purifying to obtain a compound having a structure as shown in formula I; Preferably, the solvent comprises dimethylformamide; Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin to the solvent is 1:(18-22); Preferably, the mass ratio of the 5,7-dihydroxy-4-methylcoumarin to potassium carbonate is 1:(7-9).

6. The solvent-free UV viscosity-reducing adhesive according to any one of claims 3 to 5, characterized in that: The step (2) specifically comprises the following steps: dissolving the compound having the structure shown in formula I in isooctyl acrylate, mixing with a catalyst and isophorone diisocyanate, reacting at 20 to 40° C. for 0.5 to 1 h, adding a hydroxyl-containing acrylate compound and performing a capping reaction at 40 to 60° C. for 4 to 6 h to obtain the polyurethane acrylate oligomer A; Preferably, the catalyst comprises dibutyltin dilaurate; Preferably, the mass ratio of the compound having the structure shown in Formula I to the catalyst is 1:(0.005-0.01).

7. The solvent-free UV viscosity-reducing adhesive according to any one of claims 1 to 6, characterized in that: The photoinitiator includes any one or a combination of at least two of 1-hydroxycyclohexyl phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenyl phosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, methyl benzoylformate, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-isopropylthioxanthone, benzoin dimethyl ether, dimethylbenzil ketal or benzophenone, and is further preferably a combination of 1-hydroxycyclohexyl phenyl ketone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

8. The solvent-free UV viscosity-reducing adhesive according to any one of claims 1 to 7, characterized in that: The tackifying resin includes any one of C5 petroleum resin, hydrogenated C5 petroleum resin, modified rosin ester resin or modified terpene resin, or a combination of at least two thereof; Preferably, the solvent-free UV viscosity-reducing adhesive comprises the following components in parts by weight: 38-55 parts of acrylate monomers, 16-32 parts of polyurethane acrylate oligomer A, 18-30 parts of polyurethane acrylate oligomer B, 2-5 parts of photoinitiator and 5-10 parts of tackifying resin.

9. A method for preparing a solvent-free UV viscosity-reducing adhesive as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: mixing acrylate monomers, polyurethane acrylate oligomer A, polyurethane acrylate oligomer B, a photoinitiator and a tackifying resin to obtain the solvent-free UV viscosity-reducing adhesive.

10. A UV anti-adhesive tape, characterized in that: The UV anti-viscosity tape comprises a UV anti-viscosity adhesive layer made of the solvent-free UV anti-viscosity adhesive as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • UV viscosity-reducing adhesive tape for wafer, preparation method of UV viscosity-reducing adhesive tape for wafer and UV viscosity-reducing adhesive tape for wafer

    CN115197663A

  • UV viscosity-reducing adhesive and preparation method thereof, and UV viscosity-reducing adhesive tape and preparation method thereof

    CN115746757A